Leadership and Organizational Climate on Employee Performance: A Review of Literature Studies - Anis Naki (West Science Business and Management, 2023)
This study aims to determine and analyze the influence of leadership and organizational climate on performance. This paper comes from a literature review of research articles found through Google Scholar and Semantic Scholar. The results of the literature review show that leadership and organizational climate have a significant effect on performance.